The İmpact of gonadotropin type on controlled ovarian stimulation and İntrauterine İnsemination cycle outcomes - Ozge Senem Yucel Cicek; Merve Demir (Wolters Kluwer Medknow Publications, 2022)
Background: Intrauterine insemination (IUI) combined with controlled ovarian stimulation (COS) results in higher pregnancy rates. However, there is still no consensus on the optimal COS protocol. Aims: In the present study, we aimed to analyse the effects of COS protocols with different gonadotropin types on IUI outcomes. Study Setting and Design: This was a retrospective cohort study conducted at the infertility clinic of a University hospital, including 237 COS + IUI cycles. Materials and Methods: Eligible cycles were divided into three groups according to the type of gonadotropin used for COS; cycles with recombinant follicle-stimulating hormone (rFSH) (group 1, n = 36), highly purified FSH (HP-FSH) (group 2, n = 178) and highly purified menotropin (HP-hMG) (group 3, n = 23). Clinical pregnancy rate (CPR) and live birth rate (LBR) per cycle were compared between groups. Statistical Analysis Used: The Mann-Whitney U test and Kruskal-Wallis test were used to compare numerical variables. Dunn test was used for multiple comparisons. Results: The duration of stimulation and total gonadotropin dose were similar between the three groups (P > 0.05). The CPR was 16.7% in rFSH group, 9.6% in HP-FSH group and 13.0% in HP-hMG group. The LBR was 16.7% in rFSH group, 8.4% in HP-FSH group and 13.0% in HP-hMG group. Both CPR and LBR were comparable in all three groups (P > 0.05). Conclusions: Ovarian stimulation with rFSH, HP-FSH and HP-hMG show similar COS characteristics. Furthermore, these three gonadotropin protocols for COS + IUI yielded comparable CPR and LBR. These findings suggest that all three gonadotropin types (rFSH, HP-FSH, HP-hMG) are similarly effective in COS + IUI cycles.